Effect of icon affiliation and distance moved on detection of icon position change on a situation awareness display. - Durlach PJ; Bowens LD (Military Psychology)
Continuous gradual change is often difficult to detect, although it may be easy to detect the difference between the initial and end state if directly compared. Two experiments examined people's ability to detect gradual changes in icon position on a situation awareness map. People observed sequences of icon moves that consisted of ten .9-mm colinear moves or five 8.75-mm colinear moves and reported when they noticed a change. The relatively small moves were less likely to be detected than the relatively large moves; however, an entire sequence of the .9 mm moves was rarely missed. Green icon moves were significantly less likely to be detected than blue or yellow icon moves. This may have been due to the stimulus features of the icons or those features in interaction with the map background. Various methods that might assist icon change detection are discussed.